Ruang Kelas Sekolah Dasar Sebagai Hunian Sementara di Kawasan Rawan Gempa di Selatan Jawa - rita laksmitasari rahayu (Universitas Indraprasta PGRI, 2019)
School building that has the function as a elementary school, also has the function as a temporary housing (hunian sementara/huntara). It has to have the requirements on buildings’ solidity against earthquake and also the requirements for classrooms so that the space can be used with safety and comfort. The building’s power in overcoming failures that happen on the wall has to be a requirement for durability against earthquake, among them is the power of overcoming ductility failure perpendicularly and shear failure. Efficiency of material usage and column positioning are the reasoning behind calculation of columns’ distance in the classroom. The requirements for the room include the visibility for the students towards the teacher and whiteboard and the teacher’s ability on being mobile inside the class. Those requirements are also the considerations taken into account for classroom area calculation. Huntara module unit (2x2,5)m2 is calculated to generate the minimum area for shelter in emergency situation but with safety and comfort. Huntara module unit is adapted by considering the area measurement of the classroom that has met the requirements for building solidity against the earthquare and comfortable usage of space by user. The size of a class is (7,5x5) m2 for 28 students and can be converted into 6 huntara module unit.